(untitled) (Raparin Journal of Humanities (RJH), 2024)
The Iran-Iraq war began in 1980 and lasted for eight years, and there were many reasons behind that war, but the most important of them is Iran’s attempt to export its Islamic Shiite revolution to Iraq and then to other Gulf countries, and this was a reason for these countries, especially Kuwait, to provide material support logistical, media, etc., to Iraq during the war period, and that cost Kuwait a lot, as it was exposed during the war years, especially during the period (1983-1985), to a lot of sabotage and political assassinations, the most dangerous of which was the explosions in the American embassy and the French embassy in 1983 In addition to that, the attempt to assassinate its Emir, Sheikh Jaber Al-Ahmad Al-Sabah, in 1985.